2009
DOI: 10.1007/s10072-009-0023-0
|View full text |Cite
|
Sign up to set email alerts
|

Widely varying TNF-α levels in patients with myasthenia gravis

Abstract: Animal studies have indicated an important role of tumor necrosis factor-alpha (TNF-a) in the pathogenesis of myasthenia gravis (MG), and trials of monoclonal antibodies that block TNF-a have shown clinical improvement. However, before a TNF-a blocking agent is proposed for treatment of MG, whether serum TNF-a level correlates with the patient's condition should be confirmed. Therefore, we evaluated the relationship between the serum TNF-a level and clinical factors, including the quantitative MG score and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In previous years, a number of risk genes of MG have been identified, including circulating interleukin (IL)-17A, which was identified to be increased in patients with MG compared with normal controls, and increases of IL-17A were associated with general muscle weakness (3). Tumor necrosis factor-α (TNF-α) is considered to be one of the most important cytokines in the pathogenesis of autoimmune MG, and the inhibition of TNF-α may have significant clinical efficacy for MG (4). Furthermore, chemokine CC motif receptor (CCR) 9 and CCR7 have been demonstrated to be abnormally expressed at different thymocyte stages of MG, and the overexpression of CCR9 and CCR7 in CD4-CD8-double negative thymocytes is associated with abnormal intrathymic T-cell differentiation in patients with MG (5).…”
Section: Introductionmentioning
confidence: 99%
“…In previous years, a number of risk genes of MG have been identified, including circulating interleukin (IL)-17A, which was identified to be increased in patients with MG compared with normal controls, and increases of IL-17A were associated with general muscle weakness (3). Tumor necrosis factor-α (TNF-α) is considered to be one of the most important cytokines in the pathogenesis of autoimmune MG, and the inhibition of TNF-α may have significant clinical efficacy for MG (4). Furthermore, chemokine CC motif receptor (CCR) 9 and CCR7 have been demonstrated to be abnormally expressed at different thymocyte stages of MG, and the overexpression of CCR9 and CCR7 in CD4-CD8-double negative thymocytes is associated with abnormal intrathymic T-cell differentiation in patients with MG (5).…”
Section: Introductionmentioning
confidence: 99%
“…6 It has been evidenced to act as a critical role in the MG pathogenesis, and TNF-α-blocking agents have shown significant clinical efficacy and are proposed for MG treatment. 7 TNF-α gene promoter polymorphisms have been demonstrated to be closely linked with disease pathology. To list a few, TNF-α -1031T/C and -863C/A polymorphisms are closely associated with the risk, clinical manifestation and progression of thyroid-associated ophthalmopathy (TAO).…”
Section: Introductionmentioning
confidence: 99%
“…However, MG is mainly caused by thymoma and may also be related to other kind of cancers, which implies that GO functions may be key factors for the treatment of MG. We can see that GO term of GO:0051092 was associated with all of the candidate drugs through TNF . A study showed that TNF was one of the most important cytokines in the mechanism of MG, and inhibiting TNF may exert notable clinical efficacy for MG [43], which indicates that TNF may be a significant therapeutic target in the future. We summarized the information on target genes among the 5 candidate drugs and immune-unrelated GO functions in S4 Table.…”
Section: Resultsmentioning
confidence: 99%